IDENTIFICATION OF ANIMAL-VEHICLE COLLISIONS HOTSPOTS ON HIGHWAY М-18 - Kokhan, Oleh; Movchan, Yaroslav; Gulevets, Dmytro (Proceedings of National Aviation University, 2015)
In the article we evaluate the deviation between actual location of the animal-vehicle collision and its models which were rounded up to a certain numbers. The authors use three methods: a.) graphical analysis comparing the values models location on the single coordinate plane; b.) the comparison of their absolute and relative error; c.) the comparison of the class frequency for the values of the models locations.